Immigration and crime: the effects of immigration on criminal behavior - Stowell, Jacob I. (The new Americans, 2007)
Introduction : reconsidering the link between immigration and crime -- Social disorganization theory : expectations and empirical realities -- Studies of immigration and crime : findings and limitations of previous research -- Analytical approach : data and methodology employed in current study -- Structural and spatial contexts of violence -- Direct and indirect effects of immigration on violence -- Conclusion : review and directions for future research